IMPACT OF PALM OIL BASED BIODIESEL INDUSTRY DEVELOPMENT ON PALM OIL PLANTATION AND ITS INDUSTRY IN INDONESIA - Rafian Joni, E. Gumbira Sa'id, Harianto dan Nunung Kusnadi (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT  The increase in crude oil price may disturb Indonesian macroeconomic indicators. As the biggest crude palm oil producer in the world, Indonesia can develop palm oil based biodiesel to reduce the negative impact of crude oil price increase. Palm oil based biodiesel development can influence palm oil plantation and palm oil industry and its downstream industry. By using econometric models, this study found that palm oil based biodiesel industry development will give positive impact on palm oil plantation and palm oil industry and give negative impact on palm oil downstream industry in Indonesia. Simulation can be applied to know the impact of policy on palm oil plantation, palm oil industry and palm oil downstream industry in Indonesia by palm oil based biodiesel industry development. The result of this simulation can be used to formulate the best policy for palm oil based biodiesel industry development. It shows  that when government expenditure and the export tax increase while the interest rate decreases, a higher positive impact will be in favor to palm oil plantation, palm oil industry and palm oil downstream industry. However the rise in export  tax can reduce the area of palm oil plantation. Keywords: palm oil based biodiesel industry, palm oil plantation, palm oil industry, econometric models